Rise of violent Christian extremism : whither inter-religious ties? - Hedges, Paul (2021)
The case of a self-radicalised Christian youth planning to attack two mosques in Singapore highlights the global nature of an extremist threat that may manifest as ethno-religious supremacism or as faith-driven. How will this affect inter-religious relations?